Environmental Management Accounting in the Malaysian Manufacturing Sector - Ong, Janice; Noordin, Raman; Jaidi, Junainah (Asian Journal of Accounting Perspectives, 2020)
Research aim: This research investigates the relationship between EMA (monetary and physical) and environmental performance Design/ Methodology/ Approach: This is a questionnaire-based survey study whereby the questionnaires are sent to 69 large manufacturing companies in Malaysia that are certified with ISO 14001 Environmental Management System. Research finding: The study found no relationship between EMA (monetary and physical) and environmental performance. Theoretical contribution/ Originality: The study highlights that the EMA literature is not yet comprehensive and as such, may result in the lack of a relationship with EMA. Practitioner/ Policy implication: The results suggest that a formal environmental management accounting by the government may be able to assist to the lack of relationship between EMA and environmental performance. Limitation/ Implication: The study sampled only large Malaysian manufacturing companies with ISO 14001 Environmental Management System. Additionally, a larger sample size may provide better results. Type of article: Research paper Keywords: Environmental Performance, Monetary Environmental Management Accounting, Physical Environmental Management Accounting, ISO 14001 Environmental Management System JEL Classification: C30